Bateaux, plateaux, arsenaux : quels enjeux géopolitiques dans un Arctique en mutation ? - Frédéric Lasserre (VertigO, 2021)
Three major and very different controversies oppose the countries of the Arctic. First, there is the question of the status of the potential maritime routes of the Northwest and Northeast Passages, while scenarios predict an increase in navigation. Next, there is the question of the extension of economic sovereignty over the continental shelves, beyond the 200 nautical mile line, and the border disputes that overlap could give rise to. Finally, fueled by the concern of the Arctic States to assert their control over the maritime areas that are freeing from the ice, security policies sometimes appear as a militarization of the Arctic, in particular for Russia and, for a time, for Canada. These three controversies differ as much in stakes as in the fact of changing alliance games. But do these phenomena really reflect a surge in geopolitical issues for the Arctic ?